A novel fault-detection methodology of proposed reduced switch MLI fed induction motor drive using discrete wavelet transforms - Veerendra, A. S.; Mohd Rusllim, Mohamed; Sekhar, Chavali Punya (John Wiley & Sons Ltd, 2021)
Induction motors are typically promoted in industrial applications by adopting energy-efficient power-electronic drive technology. Multilevel inverters (MLI) have been widely recognized in recent days for high-power, medium-voltage-efficient drives. There has been vital interest in forming novel multilevel inverters with reduced switching elements. The newly proposed reduced-switch five-level inverter topology extends with fewer switches, low dv/dt stress, high efficiency, and so on, over the formal multilevel inverter topologies. The multilevel inverter's reputation is greatly affected due to several faults on switching elements and complex switching sequences. In this paper, a novel fault identification process is evaluated in both healthy and faulty conditions using discrete-wavelet transform analysis. The discrete wavelet transform utilizes the multi-resolution analysis with a feature extraction methodology acquired for fault identification over the classical methods. A novel fault identification scheme is implemented on reduced-switch five-level MLI topology using the Matlab/Simulink platform to increase the drive system's reliability. The effectiveness of simulation outcomes is illustrated with proper comparisons. The pro posed topology's hardware model is implemented using a dSPACE DS1103 real-time digital controller and the results of the experiment are presented.